2006
DOI: 10.1158/0008-5472.can-06-0450
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Neurotensin and NT1 Receptor in Human Breast Cancer: A Potential Role in Tumor Progression

Abstract: Emerging evidence supports neurotensin as a trophic and antiapoptotic factor, mediating its control via the highaffinity neurotensin receptor (NT1 receptor) in several human solid tumors. In a series of 51 patients with invasive ductal breast cancers, 34% of all tumors were positive for neurotensin and 91% positive for NT1 receptor. We found a coexpression of neurotensin and NT1 receptor in a large proportion (30%) of ductal breast tumors, suggesting a contribution of the neurotensinergic signaling cascade wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
162
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(170 citation statements)
references
References 43 publications
8
162
0
Order By: Relevance
“…Further studies are needed to fully clarify the association between these results and the family of small Rho-like GTPases, including Rho, Rac, and Cdc42, that are involved in epithelial cell migration and invasion. 33 We also found that NTSR1 existed in LNCaP cells and that neurotensin, a neuroendocrine factor, induced the 21 reported that NTSR1 agonist-induced motility of breast cancer cell line MDA-MB-231 was blocked by selective inhibitors, including drugs targeting mitogen-activated protein kinase (MAPK), protein kinase C (PKC), and PLCg. They also showed that neurotensin-induced cell invasion involved the activation of matrix metalloproteinase-9 (MMP-9).…”
Section: Gelsolin-mediated Invasion Of Prostate Cancer K Hashimoto Et Almentioning
confidence: 90%
See 1 more Smart Citation
“…Further studies are needed to fully clarify the association between these results and the family of small Rho-like GTPases, including Rho, Rac, and Cdc42, that are involved in epithelial cell migration and invasion. 33 We also found that NTSR1 existed in LNCaP cells and that neurotensin, a neuroendocrine factor, induced the 21 reported that NTSR1 agonist-induced motility of breast cancer cell line MDA-MB-231 was blocked by selective inhibitors, including drugs targeting mitogen-activated protein kinase (MAPK), protein kinase C (PKC), and PLCg. They also showed that neurotensin-induced cell invasion involved the activation of matrix metalloproteinase-9 (MMP-9).…”
Section: Gelsolin-mediated Invasion Of Prostate Cancer K Hashimoto Et Almentioning
confidence: 90%
“…Several reports have shown that neurotensin and NTSR1 are implicated in the progression of pancreas, prostate, colon, and lung cancers. [20][21][22] Activation of NTSR1 is known to be involved in phosphatidyl inositol hydrolization. This pathway leads to the release of calcium ions into the cytoplasm from intracellular stores within the endoplasmic reticulum (calcium mobilization).…”
mentioning
confidence: 99%
“…[49][50][51][52] Therefore, these types of neoplasia are potential targets for NT-polyplex transfection and open the possibility of exploring new approaches of gene therapy for cancer. …”
Section: Discussionmentioning
confidence: 99%
“…One team showed that 91% of invasive ductal breast carcinomas were positive for NTSR 1 (16). Also, the level of expression of NTSR 1 was positively correlated with tumor size, Scarff-Bloom-Richardson grade, number of metastatic lymph nodes, recurrence, and survival (17).…”
Section: Breast Cancermentioning
confidence: 99%